New species of Myopsocidae (Insecta: Psocodea: “Psocoptera”) from Colombia - González-Obando, Ranulfo; Calderón-Martínez, Nadia R.; Carrejo-Gironza, Nancy S. (Zootaxa, 2023)
To broaden the knowledge of the diversity of Myopsocidae (Psocomorpha: Psocetae) in the neotropical region, a review of specimens collected in the last 12 years by the Entomological Research Group (GIE) was carried out. Twenty-six species belonging to the genera Lichenomima and Myopsocus were found, of which 22 are new to science and are here described and illustrated, they are: Lichenomima bonaverensis n. sp., L. gorgonaensis n. sp., L. guapiensis n. sp., L. huilensis n. sp., L. iscuande n. sp., L. lienhardi n. sp., L. occidentalis n. sp., L. pearmani n. sp., Myopsocus amacayacu n. sp., M. amazonensis n. sp., M. andaquies n. sp., M. caliensis n. sp., M. caquetensis n. sp., M. chocoensis n. sp., M. colombianus n. sp., M. garcialdretei n. sp., M. inga n. sp., M. insularis n. sp., M. katios n. sp., M. panchei n. sp., M. putumayensis n. sp. and M. tukunare n. sp. Four species, L. onca Mockford, L. ariasi (New), M. minor (New & Thornton) and M. minutus (Mockford), are also recorded from Colombia. A key for the determination of South American species is also presented.